Strategi Komunikasi Pelayanan PT Jasamarga Tollroad Operator dalam Meningkatkan Kepuasan Pengguna Jalan Gerbang TOL Kapuk Ruas Sedyatmo - Raihan Nugroho Pratama; Murtiadi Murtiadi; Andi Banus Achir (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Service quality at toll gates is determined not only by smooth transaction processes but also by effective communication between officers and road users. PT Jasamarga Tollroad Operator, as the toll road operational manager, is required to implement effective service communication strategies to improve road user satisfaction. This study aims to analyze the service communication strategy implemented by PT Jasamarga Tollroad Operator in improving road user satisfaction at the Kapuk Toll Gate on the Sedyatmo Toll Road. This research employed a qualitative approach using a descriptive method. Informants were selected through purposive sampling, consisting of a Customer Service Supervisor, a Customer Service officer, and road users. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the service communication strategy has been implemented through pre-operational briefings, clear information delivery, polite and understandable language, and communication media such as Variable Message Signs (VMS), the Travoy application, and the 133 Call Center. These strategies are supported by responsive, communicative, and professional officers, contributing positively to road user satisfaction, although improvements in the speed of information delivery during certain traffic conditions are still required.